2015
DOI: 10.1098/rsos.150127
|View full text |Cite
|
Sign up to set email alerts
|

Nest inundation from sea-level rise threatens sea turtle population viability

Abstract: Contemporary sea-level rise will inundate coastal habitats with seawater more frequently, disrupting the life cycles of terrestrial fauna well before permanent habitat loss occurs. Sea turtles are reliant on low-lying coastal habitats worldwide for nesting, where eggs buried in the sand remain vulnerable to inundation until hatching. We show that saltwater inundation directly lowers the viability of green turtle eggs (Chelonia mydas) collected from the world's largest green turtle nesting rookery at Raine Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 22 publications
(53 reference statements)
3
50
0
1
Order By: Relevance
“…Significant losses of 8%–65% of nesting habitat are predicted for several sea turtle rookeries, under climate change scenarios of median severity (Baker, Littnan, & Johnston, ; Fish et al., , ; Fuentes, Limpus, Hamann, & Dawson, ; Katselidis, Schofield, Stamou, Dimopoulos, & Pantis, ). Additionally, temporary inundation of beaches, associated with the increasing prevalence and intensity of storms, is expected to lower hatching success (Pike, Roznik, & Bell, ; Van Houtan & Bass, ). It is yet uncertain whether sea turtles will be able to adapt to the current rapid changes, but they have certainly endured climate change in the past (Poloczanska et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Significant losses of 8%–65% of nesting habitat are predicted for several sea turtle rookeries, under climate change scenarios of median severity (Baker, Littnan, & Johnston, ; Fish et al., , ; Fuentes, Limpus, Hamann, & Dawson, ; Katselidis, Schofield, Stamou, Dimopoulos, & Pantis, ). Additionally, temporary inundation of beaches, associated with the increasing prevalence and intensity of storms, is expected to lower hatching success (Pike, Roznik, & Bell, ; Van Houtan & Bass, ). It is yet uncertain whether sea turtles will be able to adapt to the current rapid changes, but they have certainly endured climate change in the past (Poloczanska et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Shifts may also occur at a more regional scale. There has been a northward shift in loggerhead sea turtle (Caretta caretta) nests along Melbourne Beach, Florida, the largest loggerhead turtle rookery in the Atlantic Ocean, likely due to warming temperatures (Reece et al 2013b (Fuentes et al 2010;Katselidis et al 2014;Pike et al 2015). For example, it is projected that Melbourne Beach will decrease in area by 43% from 1986 to a future with 0.5 m of sea level rise; this will restrict nesting to narrow beaches, increasing risk of erosion and crowding resulting in nests overlapping with each other (Reece et al 2013b (Pike 2013;.…”
Section: Species Highlight -Sea Turtles and Climate Changementioning
confidence: 99%
“…Microorganisms inhabit the beachrock in the form of epilithic mats on the surface ( Figure 2C), as euendolithic communities boring into sediment grains, and as cryptoendolithic communities in the interstices within the beachrock ( Figure 2D). Pike et al (2015) found that although the microbial community composition varied by location in the beachrock, it is typically dominated by non-heterocystous cyanobacteria. For the present study, samples were collected to include both the older re-cemented blocks and an associated younger beachrock that held the older blocks in place at the time of sampling ( Figure 2B).…”
Section: Heron Island Beachrockmentioning
confidence: 99%